Characteristics of immunological events in Epstein-Barr virus infection in children with infectious mononucleosis - Zhang, Yunyun; Huang, Chengrong; Zhang, Hao; Duan, Zhi; Liu, Qian; Li, Jianfei; Zong, Qiyin; Wei, Yu; Liu, Futing; Duan, Wanlu; Chen, Liwen; Zhou, Qiang; et al. (Frontiers in Pediatrics, 2023)
Backgrounds & Aims： Epstein-Barr virus (EBV) infection occurs commonly in children and causes acute infectious mononucleosis (AIM) and various malignant disease. Host immune responses are key players in the resistance to EBV infection. We here assessed the immunological events and laboratory indicators of EBV infection, as well as determined the clinical usefulness of evaluating the severity and efficacy of antiviral therapy in AIM patients. Methods： We enrolled 88 children with EBV infection. The immune environment was defined by immunological events such as frequencies of lymphocyte subsets, phenotypes of T cells, and their ability to secrete cytokines, etc. This environment was analyzed in EBV-infected children with different viral loads and in children in different phases of infectious mononucleosis (IM) from disease onset to convalescence. Results: Children with AIM had higher frequencies of CD3+ T and CD8+ T cells, but lower frequencies of CD4+ T cells and CD19+ B cells. In these children, the expression of CD62L was lower and that of CTLA-4 and PD-1 was higher on T cells. EBV exposure induced granzyme B expression, but reduced IFN-γ secretion, by CD8+ T cells, whereas NK cells exhibited reduced granzyme B expression and increased IFN-γ secretion. The frequency of CD8+ T cells was positively correlated with the EBV DNA load, whereas the frequencies of CD4+ T cells and B cells were negatively correlated. During the convalescent phase of IM, CD8+ T cell frequency and CD62L expression on T cells were restored. Moreover, patient serum levels of IL-4, IL-6, IL-10, and IFN-γwere considerably lower throughout the convalescent phase than throughout the acute phase. Conclusion: Robust expansion of CD8+ T cells, accompanied by CD62L downregulation and PD-1 and CTLA-4 upregulation on T cells, enhanced granzyme B production, and impaired IFN-γ secretion, is a typical characteristic of immunological events in children with AIM. Noncytolytic and cytolytic effector functions of CD8+ T cells are regulated in an oscillatory manner. Furthermore, the AST level, number of CD8+ T cells, and CD62L expression on T cells may act as markers related to IM severity and the effectiveness of antiviral treatment.